2015
DOI: 10.1186/s12906-015-0779-0
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activities of aqueous ethanol and n-butanol fraction of Moringa stenopetala leaves in streptozotocin-induced diabetic rats

Abstract: BackgroundMoringa stenopetala has been used in traditional health systems to treat diabetes mellitus. The aim of this study was to investigate the antidiabetic activity of aqueous ethanol and n-butanol fraction of Moringa stenopetala leaves in streptozotocin (STZ) induced diabetic rats.MethodsThe aqueous ethanol extract and n-butanol fraction of Moringa stenopetala leaves hydroalcoholic (500 mg/kg body weight) and metformin (150 mg/kg body weight) were administered to diabetic rats. Blood glucose, lipid profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 20 publications
10
106
1
1
Order By: Relevance
“…In the first 60 minutes, the BGL decrease by BFPP is even greater than those presented by the whole extract. This fact suggests that the active hypoglycemic compounds of calyces from P. peruviana extract are in the butanolic fraction similar to reported to other plants (Borar et al, 2011;Toma et al, 2015;Ibrahim and Islam, 2017). According to previous reports that identify rutin as major flavonoid in the hydroethanolic extract of calyces from P. peruviana and the evidence of hypoglycemic effect of this compound and its role in the glucose homeostasis by different mechanisms like secretagogue of insulin and stimulating of glucose uptake in muscle (Kappel et al, 2013a;, is possible to relate this flavonoid to the observed effect.…”
Section: The Content Of Rutin In P Peruviana Calyces Extract and Frasupporting
confidence: 81%
“…In the first 60 minutes, the BGL decrease by BFPP is even greater than those presented by the whole extract. This fact suggests that the active hypoglycemic compounds of calyces from P. peruviana extract are in the butanolic fraction similar to reported to other plants (Borar et al, 2011;Toma et al, 2015;Ibrahim and Islam, 2017). According to previous reports that identify rutin as major flavonoid in the hydroethanolic extract of calyces from P. peruviana and the evidence of hypoglycemic effect of this compound and its role in the glucose homeostasis by different mechanisms like secretagogue of insulin and stimulating of glucose uptake in muscle (Kappel et al, 2013a;, is possible to relate this flavonoid to the observed effect.…”
Section: The Content Of Rutin In P Peruviana Calyces Extract and Frasupporting
confidence: 81%
“…DM is a main cause of morbidity and mortality worldwide [2]. It is considering a metabolic disorder characterized by hyperglycemia, which caused by the deficiency in insulin secretion within type 1 diabetes (T1DM), and it is the main a feature of uncontrolled type 2 diabetes (T2DM) along with insulin resistance.…”
mentioning
confidence: 99%
“…The effect of combination treatment was significantly decreased the levels of SGPT, SGOT and TP liver enzyme levels when compared to the disease control rats and monotherapy of antidiabetic drug indicated improvement in liver dysfunctions. Toma et al, in the study on Moringa stenopetala leaves extracts in rats claimed considerably reduced in the hepatic enzymes levels that cause liver damage [84].…”
Section: Discussionmentioning
confidence: 99%